Klasterisasi Teknik Promosi dalam Meningkatkan Mutu Kampus Menggunakan Algoritma K-Medoids - Surya Darma (Jurnal Informatika Ekonomi Bisnis, 2021)
Promotion technique is one of the methods used by AMIK and STIKOM Tunas Bangsa Pematangiantar in finding new students. By developing promotional techniques that are more effective and efficient, it can produce the information needed to get new student candidates. The data that is processed in this research is the data of new student candidates who come from the AMIK New Student Admissions (PMB) and STIKOM Tunas Bangsa Pematangsiantar. Based on promotional data in 2020, there are several promotions carried out, including through print media, banners, collaboration with SMA / SMK schools in Pematangsiantar city, through alumni, and the web. Furthermore, the data is processed using Rapidminer software. The processing stages are grouped using the K-Medoids algorithm on the data of prospective students, including name, place and date of birth, address, religion, cellphone number, school origin, choice of study program and source of information. Followed by the process of improving the data so that more accurate data is obtained to be processed. The results of the testing of this method are knowing which regions are applying to AMIK and STIKOM Tunas Bangsa Pematngsiantar which are grouped into 2 clusters, namely the highest and the lowest. The K-Medoids algorithm that is used makes a big contribution by providing new information that can be used as a reference for AMIK and STIKOM Tunas Bangsa Pematngsiantar in terms of Promoting New Student Admissions in the coming year.